The proprietary rights status of the apartment units held by foreign nationals in Job Creation Law - Solehuddin, Solehuddin (Faculty of Law, University of Muhammadiyah Malang, 2022)
The objective of this research is to examine how the polemics of the proprietary rights of apartment units are provided by the government for foreign nationals who temporarily reside in Indonesia to encourage the improvement of investment, especially in the property sector. This research employed normative-juridical methods by conducting library research involving books, journals or scientific articles, internet media, and statutory approach involving Law No. 20 the year of 2011 regarding Apartment Units, the Law on Job Creation. This research has learned that the Proprietary Rights granted by foreign nationals staying in Indonesia refer to property rights to own apartment units or apartment unit spaces, excluding the land underneath based on land rights, namely Proprietary Rights, Building Rights, and Usufructuary Rights. Granting the status of Proprietary Rights means that the foreign nationals who obtained apartments have the same rights as Indonesian citizens do. The ownership status of Property Rights is granted to foreign nationals. The government in its program of providing apartments for the Low-Income Communities (LIC) should also give legal certainty to the communities. Due to the large number of investors entering Indonesia, it is feared that procurement of apartments for the LIC will be marginalized by the construction of Apartments special for foreign nationals. Therefore, the government should determine which areas may be allowed for foreign nationals’ ownership, where in fact the expansion of this proprietary status is an implication of the economic sector for business interests in the property sector.